Consequence of products from oxidative coupling of methane in a non-oxidative high temperature environment. Issue 7 (8th March 2023) - Komada, Haruka; Obata, Keisuke; Li, Duanxing; Sarathy, S. Mani; Takanabe, Kazuhiro
Abstract : Oxidative coupling of methane (OCM) is an exothermic reaction that results in the temperature rise towards the latter part of the reactor. This study reports the consequence of OCM product distribution after O2 depletion at high temperatures. Abstract : Oxidative coupling of methane (OCM) is a direct process that converts methane to higher hydrocarbons, such as ethylene. For several decades, various catalysts and their reaction mechanisms have been investigated to obtain high selectivity for the target products. However, the consequences of OCM products after O2 depletion at high temperatures, which is generated by an exothermic reaction, have been often overlooked. In the present study, a two-stage reactor that mimics an industrial reactor was used to study the successive reactions of OCM products. Gas phase homogeneous and heterogeneous reactions on the surface of catalysts and supports have been systematically investigated. Dehydrogenation of OCM products to acetylene and the following condensation occurs in the gas phase. Meanwhile, steam reforming of OCM products concurrently followed by water gas shift reactions was observed on various catalysts and supports and led to the loss of C2 yield. Based on the investigations, a design guideline for the OCM reactor is proposed.